Evaluation of Load-To-Strength Ratios in Metastatic Vertebrae and Comparison With Age- and Sex-Matched Healthy Individuals - Anderson, Dennis E.; Groff, Michael W.; Flood, Thomas F.; Allaire, Brett T.; Davis, Roger B.; Stadelmann, Marc A.; Zysset, Philippe K.; Alkalay, Ron N. (Frontiers in Bioengineering and Biotechnology, 2022)
Vertebrae containing osteolytic and osteosclerotic bone metastases undergo pathologic vertebral fracture when the lesioned vertebrae fail to carry daily loads. We hypothesize that task-specific spine loading patterns amplify the risk of pathologic vertebral fracture, with the degree of risk higher in osteolytic than osteosclerotic vertebrae. To test this hypothesis, we obtained clinical CT images of 11 cadaveric spines with bone metastasis, estimated the individual vertebrae strength from the CT, and created spine-specific musculoskeletal models from the CT data. We established a musculoskeletal model for each spine to compute vertebral loading for natural standing, natural standing+weights, forward flexion+weights, and lateral bending +weights and derived the individual vertebral load-to-strength ratio (LSR). For each activity, we compared the metastatic spines' predicted LSR values to normative LSR values generated from a population-based sample of 250 men and women of comparable ages. Bone metastases classification significantly affected the CT-estimated vertebral strength (Kruskal-Wallis, p<0.0001). Post-test analysis showed osteosclerotic and mixed metastases vertebrae estimated strength significantly higher than osteolytic (p=0.0016 and p=0.0003) or vertebrae without radiographic evidence of bone metastasis (p=0.0010 and p=0.0003). Compared to the normative data set 50% median LSR values, osteolytic vertebrae had higher median (50%) LSR values in natural standing (p=0.0375), natural standing + weights (p=0.0118), and lateral bending + weights (p=0.0111). Surprisingly, vertebrae showing minimal radiographic evidence of bone metastasis presented significantly higher median (50%) LSR under natural standing (p<0.0001) and lateral bending + weights (p=0.0009), than the normative data set. Osteosclerotic vertebrae had lower median (50%) LSR values under natural standing (p<0.0001), natural standing + weights (p=0.0005), forward flexion+ weights (FL+W, p<0.0001), and lateral bending + weights (p=0.0002), a trend shared by vertebrae with mixed lesions. This study is the first to apply musculoskeletal modeling to estimate individual vertebral loading in pathologic spines and highlights the role of task-specific loading in augmenting PVF risk associated with specific bone metastatic types. Our finding of a high LSR in vertebrae without radiologically observed bone metastasis highlights that patients with metastatic spine disease could be at increased risk of vertebral fractures even at levels where lesions have not been identified radiologically.